2006
DOI: 10.1002/qua.21063
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the reaction of alkynes with furan catalyzed by AuCl3 and AuCl

Abstract: ABSTRACT:A general scheme for the endo-and exo-cyclization of furan reactivity with [l-Au III, ICl x ] with (x ϭ 3, 1 and l-acetylene and vinylidene) complexes is investigated using density functional theory (DFT) code. Two conceivable mechanisms via a [4 ϩ 2] Diels-Alder process or carbene complex are analyzed. According to the activation energy values of the gold (III and I) catalyst, the first mechanism, which implies the Diels-Alder reaction of Au III , is thermodynamically favored and gives more evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Several studies have invoked their intermediacy, 4 but later calculations suggested alternative pathways. 5 The only exception is the formation of gold β-halovinylidene intermediates via AuCl-promoted [1,2]-halo migration of terminally halogenated alkynes (i.e., haloalkynes), 4d which was later supported by DFT calculations. 6 For synthetic usefulness, terminal alkynes are ideal, simple starting materials to access metal vinylidenes.…”
mentioning
confidence: 94%
“…Several studies have invoked their intermediacy, 4 but later calculations suggested alternative pathways. 5 The only exception is the formation of gold β-halovinylidene intermediates via AuCl-promoted [1,2]-halo migration of terminally halogenated alkynes (i.e., haloalkynes), 4d which was later supported by DFT calculations. 6 For synthetic usefulness, terminal alkynes are ideal, simple starting materials to access metal vinylidenes.…”
mentioning
confidence: 94%
“…Indeed, an increasing number of papers concerning the use of the pre-catalyst gold or platinum in the catalytic systems [5][6][7][8][9]. It is important to notice for many catalysis reactions, there exists no direct experimental proof for most of the intermediates shown in the mechanistic proposals.…”
Section: Introductionmentioning
confidence: 99%
“…Gold catalysis underwent an impressive development and became an important tool in organic synthesis and offers new region-selectivity possibilities [4][5][6][7][8]. Considerable works were focused on a gold precursor in fundamental and applied research [2].…”
Section: Introductionmentioning
confidence: 99%
“…This synthesis is based on a sequence which included the condensation of a furfural derivative 1 and an amino acid derivative 2, the catalytic asymmetric hydrogenation of 3 and the goldcatalysed cycloisomerization to give the phenol 6 [17][18][19][20][21][22][23][24][25][26][27][28][29] as key steps.…”
Section: Introductionmentioning
confidence: 99%